2002
DOI: 10.1007/s00018-002-8411-0
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial PHB complex: roles in mitochondrial respiratory complex assembly, ageing and degenerative disease

Abstract: Although originally identified as putative negative regulators of the cell cycle, recent studies have demonstrated that the PHB proteins act as a chaperone in the assembly of subunits of mitochondrial respiratory chain complexes. The two PHB proteins, Phblp and Phb2p, are located in the mitochondrial inner membrane where they form a large complex that represents a novel type of membrane-bound chaperone. On the basis of its native molecular weight, the PHB-complex should contain 12-14 copies of both Phblp and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
252
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(271 citation statements)
references
References 65 publications
17
252
0
2
Order By: Relevance
“…2B). Prohibitin-1 (Phb-1) and -2 (Phb-2) are two ubiquitous, abundant and highly conserved proteins that play important roles as chaperones during the assembly of mitochondrial respiratory chain complexes [42,43]. They are 130 to 157 aa shorter than reggies/flotillins and consist of a single SPFH domain located at their N terminus (human Phb-1 residues 26-187; fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B). Prohibitin-1 (Phb-1) and -2 (Phb-2) are two ubiquitous, abundant and highly conserved proteins that play important roles as chaperones during the assembly of mitochondrial respiratory chain complexes [42,43]. They are 130 to 157 aa shorter than reggies/flotillins and consist of a single SPFH domain located at their N terminus (human Phb-1 residues 26-187; fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Prohibitins have an N-terminal transmembrane stretch (Phb-1 residues 11-23) preceding the SPFH domain that is cleaved off in the mature peptide, and a putative phosphorylation site at Tyr-259 [43]. Available 3D structures for human Phb-1 (1lu7.pdb model) indicate that this protein folds very differently to the SPFH domain of reggies/flotillins ( fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that the decrease in PHB1 levels correlates with a loss of mitochondrial function [48]. PHB1 functions as a chaperone-like protein for the correct folding and assembly of subunits of the mitochondrial respiratory-chain complexes, and it must be methylated inside the mitochondria before it functions [49]. Therefore, mitochondrial SAM depletion could affect electron transfer along the mitochondrial respiratory-chain and result in oxidative stress inside mitochondria, representing another possible mechanism involved in sensitization to TNF hepatotoxicity by intracellular SAH accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] PHB has been reported to repress E2F via recruitment of the repressive proteins histone deacetylase 1 (HDAC1), nuclear receptor co-repressor (N-CoR) and the chromatin-condensing proteins brahma-related gene-1 (BRG1)/brahma (Brm). 5,6 PHB can also inhibit steroidactivated nuclear receptors, such as the androgen receptor (AR) and estrogen receptor (ER).…”
Section: Introductionmentioning
confidence: 99%